The Effectiveness of the Creative Writing Learning Model Based on the Literacy Approach - Muh Faisal; Afdhal Fatawuri Syamsuddin; Ahmad Ardillah Rahman; Sayidiman Sayidiman (Vidya Karya, 2026)
In the context of enhancing students' creative story-writing skills, an effective pedagogical model is essential. This study seeks to ascertain (1) the disparity in story-writing proficiency between students utilizing a literacy-approach-based creative writing model and those who do not, and (2) the efficacy of the literacy-approach-based creative writing model. The independent variable in this study is the literacy-approach-based creative writing model, while the dependent variable is the students' story-writing ability. The research was conducted at SDN 13 Biru Watampone, Bone Regency, with the population comprising grade V students. Class VA served as the control group and class VB as the experimental group. Data collection was facilitated through a story-writing test. The Kolmogorov-Smirnov Test of Normality and the Homogeneity of Variance Test were employed to assess normality and homogeneity, respectively, using SPSS 23.0 for Windows. An independent sample t-test, with a 95% confidence level, was conducted to evaluate the differences in story-writing abilities between the control and experimental groups. The gain-score equation was utilized to assess the model's effectiveness. The findings indicate that: (1) there is a significant difference in story-writing ability between students engaged in a literacy approach-based creative writing model and those who are not, and (2) the literacy approach-based creative writing model is highly effective in enhancing students' story-writing proficiency.